Analisis Pengaruh Gaya Kepemimpinan Terhadap Motivasi dan Kinerja Dosen di Prodi PGSD Universitas Al Muslim Bireuen - Novi Sari Liani (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The purpose of this study was to find out how the influence of leadership style and its correlation to the work motivation of lecturers, the performance of lecturers in the PGSD Study Program, Al Muslim University Bireun. The formulation of the problem is how is the influence of leadership style and its correlation to lecturer work motivation and the performance of PGSD Study Program lecturers at Al Muslim Bireun University. This research is a type of quantitative research with survey research methods. Data were analyzed with SPSS version 2.6. The result of the calculation of the paired t test shows that the result of the t test on the significance value (2-tailed) of this case example is 0.00 (p <0.05). So it can be concluded that there is an influence of leadership style on lecturer work motivation. On the performance variable the significance value (2-tailed) is 0.00 (p <0.05). So it can be concluded that there is an influence of leadership style on lecturer performance. sig. Teacher work motivation is 1.00 > 0.05 so it can be concluded that leadership style has a perfect relationship with lecturer work motivation. The second table also shows the sig value. Lecturer performance scores sig. 1.00> than 0.05 so that it can be concluded that leadership style has a perfect relationship with lecturer performance.